The Interlaced Arches and the So-Called sebka Decoration: Origin and Materialisation in al-Andalus and Its Reinterpretation in Medieval Castile - Ignacio González Cavero (Arts)
In this article, I aim to address one of the most characteristic decorative elements of the Almohad period, the so-called sebka decoration. With this aim in mind and through the research carried out and the examples that have been preserved, I consider it appropriate to know the origin of this ornamental motif that is so recurrent in the Andalusian architectural panorama and to analyse not only its compositional scheme but also the different formal variants that arose around it. Furthermore, its use in other buildings in the Kingdom of Castile is a further indication that allows us to approach a scenario where cultural and artistic transfer between al-Andalus and the Christian territories was a reality.